Corrosion inhibitor for aluminum air battery and application of corrosion inhibitor
Antimony oxide in aluminum-air batteries forms a protective adsorption layer to reduce hydrogen evolution and enhance electrochemical activity, addressing corrosion issues and improving battery capacity and longevity.
Patent Information
- Application Number
- CN202411228203.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
AI Technical Summary
Existing aluminum-air batteries face issues with severe hydrogen evolution corrosion in alkaline electrolytes, leading to reduced specific capacity and shortened service life, while adding composite corrosion inhibitors can cause dendrite growth and power short circuits.
The use of antimony oxide as an inorganic corrosion inhibitor in alkaline electrolytes forms a protective adsorption layer on the aluminum anode, reducing hydrogen evolution and enhancing electrochemical activity, thereby improving battery performance.
Antimony oxide reduces self-corrosion of the aluminum anode, increases specific capacity, and extends battery life by promoting effective electron transfer and electrochemical reactions, ensuring stable discharge performance.
Smart Images

Figure CN119133727A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum-air batteries, and in particular to a corrosion inhibitor for aluminum-air batteries and application thereof. Background Art
[0002] As a green energy source, metal-air batteries have attracted extensive research interest and are considered one of the most promising new energy sources. Their energy density is significantly higher than that of lithium-ion batteries. Compared with zinc and lithium, the theoretical energy density of aluminum (8.1 kWh kg -1) is the highest. In addition, metallic lithium is highly active, easily reacts in the air, and its reserves in the earth's crust are extremely scarce. In comparison, metallic aluminum has the advantages of abundant resources, recyclability, low cost, and moderate chemical activity. Metallic aluminum is relatively active, and oxidation will occur on its surface in the air to form a protective film. Therefore, when metallic aluminum is used as the anode material of aluminum-air batteries, its corrosion potential is relatively positive. And in a neutral electrolyte, the voltage of the aluminum anode will be significantly reduced, resulting in a loss of its energy density. In comparison, on the one hand, the use of strong alkaline electrolytes such as KOH and NaOH can better dissolve the protective film on the surface of the aluminum anode. On the other hand, alkaline electrolytes with higher conductivity can increase the voltage during the operation of the aluminum-air battery, significantly improving its energy density. However, in an alkaline electrolyte, the aluminum anode will suffer from severe hydrogen evolution corrosion, which will reduce the specific capacity of the battery and shorten its service life. In response to the above key issues, the two mainstream optimization strategies are: one is to add trace elements (Mg, In, Zn, Ga, Mn, Ga, etc.) to high-purity aluminum (99.999wt%) during the smelting process. These specific alloying elements activate pure aluminum through the "dissolution and re-deposition" process on the surface of the aluminum anode, so that the aluminum-air battery increases the discharge voltage during operation. In addition, the alloying elements also have a high hydrogen evolution overpotential, which can reduce the self-corrosion of the aluminum anode. The other is to add some inorganic corrosion inhibitors and organic corrosion inhibitors to the alkaline electrolyte to achieve a similar alloying effect. Inorganic corrosion inhibitors usually have higher chemical stability and can maintain their corrosion inhibition effect under a wider range of conditions. Compared with organic corrosion inhibitors, inorganic corrosion inhibitors usually do not contain organic solvents or other ingredients that are harmful to the environment, so they are more in line with environmental protection requirements. Since inorganic corrosion inhibitors are relatively cheap and the acquisition method is relatively simple, they have a wide range of applicability. The Chinese patent application with publication number CN111293382A outlines a method of adding an ultrasonic device to a battery to increase the electrochemical activity of the aluminum anode and increase its discharge voltage during operation of the aluminum-air battery. This is because ultrasound can cause the oxide film and discharge products on the surface of the aluminum anode to fall off during vibration. However, adding an ultrasonic device to the battery is expensive, and the increased weight will reduce the operating life of the battery. The Chinese patent application with publication number CN115425335A outlines an electrolyte that increases the specific capacity of an aluminum-air battery, and adds a trifluoromethanesulfonic acid corrosion inhibitor to the electrolyte, and the optimal concentration selected is 1 mol / L. This organic corrosion inhibitor combines trifluoromethanesulfonic acid groups with water molecules and is adsorbed on the surface of the aluminum anode to provide full protection, which can reduce the corrosion of the aluminum-air battery when it is in standby mode and significantly improve its specific capacity, but the voltage boost effect is small when the battery is running. At the same time, there are also schemes using composite corrosion inhibitors in the prior art, usually using a combination of inorganic corrosion inhibitors and organic corrosion inhibitors, which will result in a high concentration of corrosion inhibitors in the electrolyte.High concentrations of composite corrosion inhibitors can cause dendrite growth of metal deposits on the surface of the aluminum electrode, resulting in a power short circuit in the assembled aluminum-air battery device, especially when the anode-cathode distance is short. It is very important to explore simple and efficient corrosion inhibitors. In actual application scenarios, the battery will encounter two mode cycles: standby and operation. How to balance the reduction of aluminum anode corrosion when stationary and increase the battery voltage when running is a problem that researchers are concerned about. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to propose a corrosion inhibitor for aluminum-air batteries and its application. The corrosion inhibitor is used in the alkaline electrolyte of aluminum-air batteries to improve the performance of aluminum-air batteries.
[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0005] A corrosion inhibitor for aluminum-air batteries, wherein the corrosion inhibitor is antimony oxide.
[0006] Pure aluminum will suffer from severe self-corrosion in alkaline electrolytes, reducing the capacity of aluminum-air batteries. However, adding an inorganic corrosion inhibitor, antimony oxide, to alkaline electrolytes can significantly reduce the rate of hydrogen evolution at the aluminum anode. Studies have shown that in an alkaline environment, antimony oxide undergoes a replacement reaction with metallic aluminum to produce antimony ions (Sb 3+ ) can form an adsorption layer containing antimony on the surface of metallic aluminum. The presence of the adsorption layer can activate the aluminum anode to a certain extent, causing it to interact more effectively with the electrolyte during the electrochemical process, thereby enhancing the electrochemical activity of the anode. The adsorption of antimony ions changes the chemical properties and active site distribution of the anode surface, making the anode surface more susceptible to reacting with dissolved oxygen or other active substances in the electrolyte, and the presence of antimony ions can change the electronic structure of the anode surface, help provide electron transfer channels, and accelerate the transmission rate of electrons on the anode surface, thereby promoting the electrochemical reaction. The adsorption layer formed by antimony ions on the anode surface has a certain protective effect, preventing the anode from direct contact with corrosive substances in the electrolyte, thereby slowing down the corrosion rate of the anode and extending its service life.
[0007] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0008] An alkaline electrolyte for an aluminum-air battery, wherein the above-mentioned corrosion inhibitor for an aluminum-air battery is added to the alkaline electrolyte.
[0009] As a preferred embodiment of the alkaline electrolyte for aluminum-air batteries described in the present invention, the concentration of the corrosion inhibitor in the alkaline electrolyte is 0.01 to 2 mol / L.
[0010] As a preferred embodiment of the alkaline electrolyte for aluminum-air batteries described in the present invention, the concentration of the corrosion inhibitor in the alkaline electrolyte is 0.03 to 1 mol / L.
[0011] As a preferred embodiment of the alkaline electrolyte for aluminum-air batteries described in the present invention, the concentration of the corrosion inhibitor in the alkaline electrolyte is 0.05 mol / L.
[0012] As a preferred embodiment of the alkaline electrolyte for aluminum-air batteries described in the present invention, the alkaline electrolyte is a KOH solution.
[0013] As a preferred embodiment of the alkaline electrolyte for aluminum-air batteries described in the present invention, the concentration of the KOH solution is 0.01 to 7 mol / L.
[0014] As a preferred embodiment of the alkaline electrolyte for aluminum-air batteries described in the present invention, the concentration of the KOH solution is 4 mol / L.
[0015] A method for preparing the alkaline electrolyte for aluminum-air batteries as described above comprises adding a corrosion inhibitor to the alkaline electrolyte and uniformly mixing the mixture in a magnetic stirrer to obtain the alkaline electrolyte for aluminum-air batteries.
[0016] As a preferred embodiment of the method for preparing an alkaline electrolyte for an aluminum-air battery described in the present invention, the temperature of the magnetic stirring is 15 to 25° C., the speed of the magnetic stirring is 450 to 550 rpm, and the time of the magnetic stirring is 15 to 25 min.
[0017] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0018] An aluminum-air battery comprises the alkaline electrolyte for aluminum-air batteries.
[0019] The beneficial effects of the present invention are as follows:
[0020] The present invention proposes a corrosion inhibitor for aluminum-air batteries and its application, which utilizes the replacement reaction between inorganic corrosion inhibitor antimony oxide and aluminum metal in an alkaline environment to form a metal adsorption layer on the surface of aluminum metal. The presence of the metal adsorption layer can activate the aluminum anode to a certain extent, allowing it to interact more effectively with the electrolyte, thereby enhancing the electrochemical activity of the anode, reducing losses, and increasing the specific capacity of the battery, thereby improving the service life and working efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0022] Figure 1 This is a diagram showing the mechanism of action of the inorganic corrosion inhibitor antimony oxide on aluminum anode corrosion inhibition of the present invention.
[0023] Figure 2 The hydrogen evolution rate results of various embodiments and comparative examples of the present invention are shown in FIG.
[0024] Figure 3 The figures are the continuous discharge results of the embodiments and comparative examples of the present invention.
[0025] Figure 4 The intermittent discharge results of various embodiments and comparative examples of the present invention are shown in FIG.
[0026] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0027] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention provides a corrosion inhibitor for aluminum-air batteries and its application, which has the following advantages:
[0029] (1) The inorganic corrosion inhibitor antimony oxide of the present invention has simple raw materials, low cost, is green and environmentally friendly, safe and reliable, and easy to operate.
[0030] (2) Adding inorganic corrosion inhibitor antimony oxide to alkaline electrolyte can reduce the self-corrosion of aluminum anode when it is stationary, and increase the capacity of aluminum-air battery. At the same time, during the discharge process, it can make the aluminum anode corrode evenly, avoid pitting corrosion and cause circuit short circuit, and greatly increase the battery operation time. This is of great significance for extending the battery life and service life of electrical equipment.
[0031] (3) The inorganic corrosion inhibitor antimony oxide of the present invention increases the battery capacity and activates the pure aluminum anode when the battery is running, so that it has higher electrochemical performance, increases the battery voltage and specific energy, and can also meet high-power service scenarios while extending the battery life.
[0032] According to one aspect of the present invention, the present invention provides the following technical solution:
[0033] A corrosion inhibitor for aluminum-air batteries, wherein the corrosion inhibitor is antimony oxide.
[0034] like Figure 1 The figure shows the mechanism of the action of inorganic corrosion inhibitor antimony oxide on aluminum anode corrosion inhibition. In alkaline electrolyte, the unevenness of aluminum surface, its own defects or the formation of surface oxides lead to the existence of a large number of hydrogen evolution sites. The existence of these hydrogen evolution sites aggravates the self-corrosion of aluminum anode and further reduces the discharge performance of the battery. However, when inorganic corrosion inhibitor antimony oxide is added to the electrolyte, antimony oxide undergoes a replacement reaction with metallic aluminum and forms an antimony-containing adsorption layer on the aluminum surface. The existence of this adsorption layer has two main functions: on the one hand, it can cover some of the hydrogen evolution sites, effectively reducing the chance of oxidation reaction between the aluminum surface and water, thereby reducing the self-corrosion rate of aluminum and reducing the loss of aluminum anode. On the other hand, the adsorption layer can activate the anode and promote it to interact more effectively with the electrolyte during the electrochemical process, thereby enhancing the electrochemical activity of the anode. Finally, the presence of antimony ions changes the electronic structure of the anode surface, helps to provide electron transfer channels, accelerates the transmission rate of electrons on the anode surface, and promotes the electrochemical reaction.
[0035] According to another aspect of the present invention, the present invention provides the following technical solution:
[0036] An alkaline electrolyte for an aluminum-air battery, wherein the above-mentioned corrosion inhibitor for an aluminum-air battery is added to the alkaline electrolyte.
[0037] Preferably, the concentration of the corrosion inhibitor in the alkaline electrolyte is 0.01 to 2 mol / L. Further preferably, the concentration of the corrosion inhibitor in the alkaline electrolyte is 0.03 to 1 mol / L. Even further preferably, the concentration of the corrosion inhibitor in the alkaline electrolyte is 0.05 mol / L.
[0038] Preferably, the alkaline electrolyte is a KOH solution. Further preferably, the concentration of the KOH solution is 0.01 to 7 mol / L. Even more preferably, the concentration of the KOH solution is 4 mol / L.
[0039] A method for preparing the alkaline electrolyte for aluminum-air batteries as described above comprises adding a corrosion inhibitor to the alkaline electrolyte and uniformly mixing the mixture in a magnetic stirrer to obtain the alkaline electrolyte for aluminum-air batteries.
[0040] Preferably, the temperature of the magnetic stirring is 15 to 25° C., the speed of the magnetic stirring is 450 to 550 rpm, and the time of the magnetic stirring is 15 to 25 min.
[0041] More preferably, the temperature of the magnetic stirring is 20° C., the speed of the magnetic stirring is 500 rpm, and the time of the magnetic stirring is 20 min.
[0042] According to another aspect of the present invention, the present invention provides the following technical solution:
[0043] An aluminum-air battery comprises the alkaline electrolyte for aluminum-air batteries.
[0044] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0045] Example 1
[0046] The aluminum-air battery and experimental method of this embodiment are as follows:
[0047] (1) In the hydrogen evolution experiment, a pure aluminum sheet with an area of 1 cm × 1 cm was used to make the anode sample required for the experiment. The bottom and sides of the sheet were wrapped with epoxy resin. The exposed aluminum surface was polished with 280, 320, 600 and 1000 mesh sandpaper respectively, and then rinsed with deionized water and anhydrous ethanol. Finally, it was dried and placed in a volumetric flask in the hydrogen evolution device.
[0048] When configuring a potassium hydroxide solution with a concentration of 4 mol / L, first put the weighed potassium hydroxide solid into a beaker for dissolution, drain it into a 1L volumetric flask after it is fully dissolved, and finally titrate to the specified scale. Then add the corresponding amount of antimony oxide to the potassium hydroxide solution at room temperature (the concentration of antimony oxide in the alkaline electrolyte is 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, and 0.07 mol / L, respectively), and stir under the conditions of a magnetic stirring temperature of 20 ° C, a magnetic stirring speed of 500 rpm, and a magnetic stirring time of 20 min to ensure uniform dissolution. Finally, the completely dissolved solution is drained into a hydrogen evolution device volumetric flask to completely immerse the aluminum anode sample and ensure that its exposed surface is facing up to reduce experimental errors.
[0049] The counting started after standing for 15 minutes, and the numerical changes were recorded every 5 minutes during the hydrogen evolution experiment. Each group of experiments lasted for 1 hour, and each group was tested three times to improve the accuracy of the experiment. The hydrogen evolution rate of each group of experiments was calculated and the average value of the three groups was taken as the final hydrogen evolution rate value.
[0050] (2) For the continuous discharge experiment, a 1cm×1cm pure aluminum sheet was used to make the required anode sample. First, one side of the aluminum sheet was polished and then soldered to a certain length of copper wire. The welded sample was wrapped with epoxy resin on the bottom and sides. After cooling and solidification, the aluminum surface not connected to the copper wire was polished with 280, 320, 600 and 1000 mesh sandpaper respectively. Then, it was rinsed with deionized water and anhydrous ethanol and blown dry. The dried anode sample was placed on an electronic balance for weighing and recording, and finally placed in a simple battery model.
[0051] When preparing a potassium hydroxide solution with a concentration of 4 mol / L, first place the pre-weighed potassium hydroxide solid in a beaker to dissolve. After it is fully dissolved, drain the solution into a 1L volumetric flask and titrate to the specified scale. Then take 100 ml of potassium hydroxide solution and pour it into a beaker, add the corresponding amount of antimony oxide (the concentration of antimony oxide in the alkaline electrolyte is 0.05 mol / L), and stir under the conditions of magnetic stirring at a temperature of 20 ° C, a speed of magnetic stirring of 500 rpm, and a time of magnetic stirring of 20 min to ensure uniform dissolution. After the antimony oxide is completely dissolved, pour the solution into a homemade simple battery model to ensure that the anode sample is completely immersed therein, then connect the wires of the blue battery system, and start a continuous discharge test.
[0052] The continuous discharge time is 6 hours, the static time before discharge is 5 minutes, and the data is recorded every 0.05 seconds. Each group of experiments is repeated three times to ensure the accuracy of the experiment. After the discharge is completed, the aluminum anode is placed in an ultrasonic cleaner for cleaning and drying, and then placed in an electronic balance for weighing and recording. Finally, the battery efficiency and specific capacity and other information are calculated based on the experimental data.
[0053] (3) The intermittent discharge experiment uses a 1cm×1cm pure aluminum sheet to make the required anode sample. First, polish one side of the aluminum sheet, and then solder it to a certain length of copper wire. The welded sample is wrapped with epoxy resin on the bottom and around, and after it cools and solidifies, the aluminum surface not connected to the copper wire is polished with 280, 320, 600 and 1000 mesh sandpaper respectively. Then, rinse with deionized water and anhydrous ethanol, and blow dry. The dried anode sample is placed in an electronic balance for weighing and recording, and finally placed in a simple battery model.
[0054] When preparing a potassium hydroxide solution with a concentration of 4 mol / L, first place the pre-weighed potassium hydroxide solid in a beaker to dissolve. After it is fully dissolved, drain the solution into a 1L volumetric flask and titrate to the specified scale. Then take 100 ml of potassium hydroxide solution and pour it into a beaker, add the corresponding amount of antimony oxide (the concentration of antimony oxide in the alkaline electrolyte is 0.05 mol / L), and stir under the conditions of 20 ° C, 500 rpm, and 20 min of magnetic stirring to ensure uniform dissolution. After the inorganic corrosion inhibitor is completely dissolved, pour the solution into a simple battery model to ensure that the anode sample is completely immersed therein, then connect the wires of the blue battery system, and start the intermittent discharge test.
[0055] During intermittent discharge, the continuous discharge time was set to 30 min, the static time was set to 30 min, the total intermittent discharge time was set to 12 h, data was recorded every 0.05 s, and each group of experiments was repeated three times to ensure the accuracy of the experiment.
[0056] Comparative Example 1
[0057] The difference from Example 1 is that the inorganic corrosion inhibitor antimony oxide is not added to the alkaline electrolyte.
[0058] Comparative Example 2
[0059] The difference from Example 1 is that potassium stannate is added to the alkaline electrolyte:
[0060] (1) During the hydrogen evolution experiment, the concentrations of potassium stannate in the alkaline electrolyte were 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, and 0.07 mol / L, respectively.
[0061] (2) During the continuous discharge experiment, the concentration of potassium stannate in the alkaline electrolyte was 0.05 mol / L.
[0062] (3) During the intermittent discharge experiment, the concentration of potassium stannate in the alkaline electrolyte was 0.05 mol / L.
[0063] Comparative Example 3
[0064] The difference from Example 1 is that sodium stannate is added to the alkaline electrolyte:
[0065] (1) During the hydrogen evolution experiment, the concentrations of sodium stannate in the alkaline electrolyte were 0.005 mol / L, 0.01 mol / L, 0.03 mol / L, and 0.05 mol / L, respectively.
[0066] (2) During the continuous discharge experiment, the concentration of sodium stannate in the alkaline electrolyte was 0.01 mol / L.
[0067] (3) During the intermittent discharge experiment, the concentration of sodium stannate in the alkaline electrolyte was 0.01 mol / L.
[0068] Comparative Example 4
[0069] The difference from Example 1 is that zinc oxide is added to the alkaline electrolyte:
[0070] (1) During the hydrogen evolution experiment, the concentrations of zinc oxide in the alkaline electrolyte were 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, and 0.07 mol / L, respectively.
[0071] (2) During the continuous discharge experiment, the concentration of zinc oxide in the alkaline electrolyte was 0.05 mol / L.
[0072] (3) During the intermittent discharge experiment, the concentration of zinc oxide in the alkaline electrolyte was 0.05 mol / L.
[0073] The experimental results of the above embodiments and comparative examples are as follows Figure 2-4 As shown, Figure 2 The hydrogen evolution rate results of each embodiment and comparative example are as follows: Figure 3 The continuous discharge results of each embodiment and comparative example are shown in FIG. Figure 4 The intermittent discharge results of various embodiments and comparative examples are shown in FIG.
[0074] from Figure 2 It can be seen that in an alkaline environment without adding corrosion inhibitor, the hydrogen evolution rate of the aluminum anode is relatively high (such as Figure 2 However, after adding the inorganic corrosion inhibitor antimony oxide (as shown in (a) Figure 2 As shown in (e), the hydrogen evolution rate of the aluminum anode is significantly reduced, and as the concentration of the inorganic corrosion inhibitor antimony oxide increases, the hydrogen evolution rate of the pure aluminum anode in the alkaline electrolyte first decreases, but then rebounds to a certain extent, resulting in an increase in the hydrogen evolution rate. When the antimony oxide concentration is 0.05 mol / L, the aluminum anode has the best corrosion inhibition effect (hydrogen evolution rate is 0.0284 ml·cm -2 ·min -1 The hydrogen evolution rate results of Comparative Examples 2-4 are as follows: Figure 2 As shown in (b)-(d). Figure 2 (f) is a comparison of the most effective hydrogen evolution effects of different corrosion inhibitors. It can be seen that when the inorganic corrosion inhibitor antimony oxide is added to the alkaline electrolyte, the hydrogen evolution rate of the pure aluminum anode is the lowest and its corrosion inhibition effect is the best.
[0075] from Figure 3 It can be seen that in an alkaline environment without adding corrosion inhibitor, the specific capacity of the aluminum anode is 2531.54 mAh g -1 However, after adding the inorganic corrosion inhibitor antimony oxide, the specific capacity of the aluminum anode reached 2959.186 mAh g-1 , the battery efficiency reaches 99%, and is better than the continuous discharge results of the aluminum anodes in Comparative Examples 2-4.
[0076] from Figure 4 It can be seen that adding sodium stannate (such as Figure 4 (b)) and zinc oxide (as shown in Figure 4 The intermittent discharge curves of (c) show abnormal fluctuations and irregular shapes, which indicates that the internal electrochemical reaction is unstable after adding these two corrosion inhibitors. Figure 4 (a)) and antimony oxide (as shown in Figure 4 The discharge curve shown in (d) is relatively smooth, indicating that the discharge voltage is stable and the battery has good performance and stability. Compared with the discharge curve of antimony oxide, the intermittent discharge curve of potassium stannate is sharper, and its open circuit potential curve is not as smooth as the discharge curve after adding antimony oxide. This indicates that the ion concentration in the electrolyte is uneven after adding potassium stannate or there is an uneven diffusion effect between the electrolyte and the electrode, resulting in instability of the open circuit potential. Comprehensive analysis shows that the battery performance is better and the stability is stronger after adding the inorganic corrosion inhibitor antimony oxide.
[0077] It can be seen from the above embodiments and comparative examples that the present invention utilizes the replacement reaction between the inorganic corrosion inhibitor antimony oxide and aluminum metal in an alkaline environment to form a metal adsorption layer on the surface of the aluminum metal. The presence of the metal adsorption layer can activate the aluminum anode to a certain extent, allowing it to interact more effectively with the electrolyte, thereby enhancing the electrochemical activity of the anode, reducing losses, and increasing the specific capacity of the battery, thereby improving the service life and working efficiency of the battery.
[0078] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A corrosion inhibitor for aluminum-air batteries, characterized in that: The corrosion inhibitor is antimony oxide.
2. An alkaline electrolyte for an aluminum-air battery, characterized in that: The corrosion inhibitor for aluminum-air battery according to claim 1 is added to the alkaline electrolyte.
3. The alkaline electrolyte for aluminum-air battery according to claim 2, characterized in that: The concentration of the corrosion inhibitor in the alkaline electrolyte is 0.01-2 mol / L.
4. The alkaline electrolyte for aluminum-air battery according to claim 3, characterized in that: The concentration of the corrosion inhibitor in the alkaline electrolyte is 0.03-1 mol / L.
5. The alkaline electrolyte for aluminum-air battery according to claim 2, characterized in that: The alkaline electrolyte is a KOH solution.
6. The alkaline electrolyte for aluminum-air battery according to claim 5, characterized in that: The concentration of the KOH solution is 0.01-7 mol / L.
7. A method for preparing an alkaline electrolyte for an aluminum-air battery according to any one of claims 2 to 6, characterized in that: The corrosion inhibitor is added into the alkaline electrolyte and the mixture is uniformly mixed in a magnetic stirrer to obtain an alkaline electrolyte for an aluminum-air battery.
8. The method for preparing an alkaline electrolyte for an aluminum-air battery according to claim 7, characterized in that: The temperature of the magnetic stirring is 15-25° C., the speed of the magnetic stirring is 450-550 rpm, and the time of the magnetic stirring is 15-25 min.
9. An aluminum-air battery, comprising the alkaline electrolyte for an aluminum-air battery according to any one of claims 2 to 6.
Citation Information
Patent Citations
Corrosion inhibitor as mercury substitute in alkaline zinc series cell
CN1147158A
Alkaline electrolyte composite corrosion inhibitor and application thereof
CN117646217A
Air conditioner for outdoor storage
KR102284342B1
